Junior high school principals’ perspectives in underdeveloped area on independent curriculum implementation in Indonesia - Kartika Yoga Eka Pratiwi Negara (Kuras Institute, 2025)
Purpose − Educational disparities in underdeveloped areas of Indonesia present significant challenges for policy implementation, including the recent introduction of the Independent Curriculum. This study explores how junior high school principals in these regions perceive and implement the curriculum, focusing on their understanding, the obstacles they encounter, and the strategies they adopt. Method − A qualitative research design was employed, with data collected through semi-structured interviews involving principals from several underdeveloped regions. Thematic analysis was conducted to identify recurring patterns and insights. Findings − The findings reveal three major areas of concern: teacher competence, school infrastructure, and parental involvement. Principals reported difficulties in implementing student-centred learning due to limited teacher training, challenges in integrating technology, and increased administrative workloads. Infrastructural limitations, such as unreliable internet access and a shortage of textbooks, further hinder curriculum delivery. Additionally, many parents are unable to support their children's learning due to work demands and unfamiliarity with the curriculum content. In response, principals have initiated various strategies, including providing internet quota assistance, conducting internal teacher training, and collaborating with local organizations. This study highlights the crucial role of school leadership in adapting national educational policies to local contexts. It underscores the need for targeted support systems and infrastructure development and calls for future comparative research across different regional contexts to inform more equitable curriculum implementation.